The relations between constipation and characteristics of intestinal morphologies by colonoscopy - Xu, Yuting; Xiao, Qili (Frontiers in Gastroenterology, 2023)
Background: Constipation is commonly diagnosed throughout the worldwide, and it is typically associated with various factors. However, data on the characteristics of intestinal morphologies linked with the constipation are scarce. We examined the association between the characteristics of intestinal morphologies and constipation. Patients and Methods: Between March 2020 and February 2021, we enrolled 510 patients from the Affiliated Zhongshan Hospital of Guangzhou University of Chinese Medicine into two groups: 260 in the constipation group and 250 in the control group. Of these patients, intestinal morphology characteristics judged by colonoscopy were compared and analyzed. Results: There were meaningful differences between the cohorts based on intestinal morphologies of tortuousness (P0.001) and dissociation (P0.001). Additionally, significance was determined for either intestinal morphologies of both tortuousness and dissociation (P0.001) or only tortuousness without conditions (P=0.015), but there was no significant difference between the two groups with respect to only dissociation without other conditions (P=0.077). Conduct subgroup analysis on statistically significant variables: gender(P0.001), age(P=0.002), and operation time(P0.001), the results showed that regardless of the subgroup analysis, there was statistical significance in tortuousness. Besides, dissociation had statistical significance for elderly men and longer operation time. Conclusion: Compared to the general population, people with intestinal morphologies of dissociation and especially tortuousness seem to more often experience constipation.